Micro-ct Assessments Of Potential Anti-osteoporotic Agents - Nadia Mohd Effendy; Mohd Fadhli Khamis; Ahmad Nazrun Shuid (Bentham Science Publisher, 2024)
Bone quality assessment is important in assessments of potential agents for the prevention and treatment of osteoporosis. Bone density, microarchitecture and strength are important determinants in osteoporotic study which are widely studied using Dual-Energy X-ray Absorptiometry (DXA), histomorphometry and radiological imaging techniques. In recent years, high resolution micro-CT has become feasible for in vitro or in vivo evaluation of bone architecture. Three-dimensional images of micro-CT reflected high correlations with the conventional histomorphometry and DXA. In comparison to other imaging techniques, micro-CT is the most effective tool in detecting early bone changes for fracture prediction and assessments of potential anti-osteoporotic agents. It is crucial to define an ideal setting with safe radiation doses and appropriate methods for image reconstruction and segmentation to obtain high resolution images. Micro-CT evaluation provides a better insight of bone structure as well as non-metric parameters such as connectivity density, structural model index (SMI) and degree of anisotropy (DA). This non- invasive imaging technique is also equipped with finite element analysis for evaluation of bone biomechanical strength. Micro-CT allows a compressive understanding of the relationships between bone density, microarchitecture and strength which is fundamental to development of pharmacological interventions.